THE EXPERIENCE OF THE USAGE OF BLOCKER OF AT1-ANGIOTENZINE RECEPTOR APROVEL ON HYPERTENSIVE PATIENTS - Dzyak, G.V.; Kolesnik, T.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The aim of  the research was to study clinical effects and acceptability of a new AT1-recepotor blocker – irbesartan (aprovel, Sanofi/BMS). 30 patients with soft and moderate arterial hypertension were examined, the average age of the examined persons is 52,6±6,1 years old, duration of disease - 9,7 years. The prescribed dose of aprovel was 150 mg per day for 12 weeks, the dose was corrected after 4 weeks of therapy. All the patients passed 24 hours’ blood pressure monitoring ( device of MEDITEX, ABPM, Hungary) before the start of treatment and on 4, 8, 12after it. The following indices were analyzed: middle systolic and diastolic blood pressure (24-hours, day, night), variability of blood pressure, hypertension time and square indices.  This study showed the efficacy of aprovel monotherapy (the dose made up 150 – 300 mg per day). The preparation causes a stable hypotensive effect, decreasing systolic and diastolic blood pressure after 6 – 8 week of treatment. The hypotensive effect of aprovel depends on the dose of the preparation. Aprovel does not influence normal circadian low daily blood pressure rhythm and corrects pathologicone.